1989
DOI: 10.3382/ps.0680522
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Concurrent Stressors in Chicks.

Abstract: Effects of multiple concurrent stressors on female Hubbard x Hubbard chicks were studied in a 2(6)-factorial experiment that employed as stressor treatments aerial ammonia (A, 0 or 125 ppm), beak trimming [B, sham handled or beak trimmed/cauterized on trial Day 1 (posthatch Day 10)], coccidiosis (X, gavage with 0 or 6 x 10(5) sporulated Eimeria acervulina oocysts), intermittent electric shock (E, 0 or between 2.9 and 8.7 mA), environmental heat stress (H, air temperature 30.4 or 34.8 C), and continuous noise (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(60 citation statements)
references
References 20 publications
(23 reference statements)
8
51
0
1
Order By: Relevance
“…The high density in the crates makes it very difficult for the birds to dissipate their heat (Metheringham and Hubrecht, 1996). The increase in heterophils/ lymphocytes ratio due to heat stress is in agreement with studies of McFarlane and Curtis (1989), Huff et al (2005) and Minka and . The H/L ratio has been used as a reliable indicator of stress in birds (Altan et al, 2000), indicating that, in our study, birds from the control group were significantly stressed compared to treated groups.…”
Section: Discussionsupporting
confidence: 75%
“…The high density in the crates makes it very difficult for the birds to dissipate their heat (Metheringham and Hubrecht, 1996). The increase in heterophils/ lymphocytes ratio due to heat stress is in agreement with studies of McFarlane and Curtis (1989), Huff et al (2005) and Minka and . The H/L ratio has been used as a reliable indicator of stress in birds (Altan et al, 2000), indicating that, in our study, birds from the control group were significantly stressed compared to treated groups.…”
Section: Discussionsupporting
confidence: 75%
“…The differences between treatments in RBC, PCV and hemoglobin were not part of the working hypotheses and warrant further investigation. The H:L ratio increases as stress increases and life quality decreases, indicating decreasing welfare status (Gross and Siegel, 1983;McFarlane and Curtis, 1989;Cravener et al, 1992). H:L ratio results showed that quails kept in BC experimented a lower welfare degree when compared to EA.…”
Section: Discussionmentioning
confidence: 95%
“…Craig and Craig (1985) did not find significant differences in glucocorticoids when comparing confinement systems. Mcfarlane and Curtis (1989) considered leucocyte responses to stressful conditions as less variable than glucocorticoid responses. Additionally, Cunningham et al (1988) and Craig and Craig (1985) reported that glucocorticoid levels might not be useful for chronic stress measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McFarlane et al (1989) and McFarlane and Curtis (1989) evaluated consequences of multiple concurrent stressors on young chickens by hematologic parameters; however, hematologic information for wild birds is limited. Lisano and Kennamer (1977) profiled eastern wild turkey (Meleagris gallopavo silvestris) blood parameters in a descriptive study without induced treatment variables.…”
Section: Introductionmentioning
confidence: 99%